2020
DOI: 10.1016/j.msea.2019.138529
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alloying with Cu and Mn and thermal treatments on the mechanical instability of Zn-0.05Mg alloy

Abstract: The detrimental effect of natural aging on mechanical properties of zinc alloys restricts their application as bioresorbable medical implants. In this study, aging of Zn-0.05Mg alloy and the effect of 0.5 Cu and 0.1 Mn (in weight percent) addition on the microstructure and tensile properties were studied. The alloys were cold rolled, aged and annealed; aiming to investigate the effects of precipitates and grain size on the mechanical properties and their stability. TEM analysis revealed that in ultrafine-grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The addition of 0.05 wt% Mg to the extruded Zn significantly increased its σ UTS to 225 MPa and its elongation (ε) to 26%, showing increases of more than ~2 times in σ UTS and ~1.9 times in ε over extruded pure Zn (with σ UTS = 112 MPa and elongation = 14%). Ardakani et al [ 179 ] reported the effects of the addition of 0.1 wt% of Mn on the microstructure ( Fig. 4 c–d) and tensile properties of binary Zn-0.05 Mg alloys.…”
Section: Microstructure Textural Evolution and Mechanical Propertiementioning
confidence: 99%
“…The addition of 0.05 wt% Mg to the extruded Zn significantly increased its σ UTS to 225 MPa and its elongation (ε) to 26%, showing increases of more than ~2 times in σ UTS and ~1.9 times in ε over extruded pure Zn (with σ UTS = 112 MPa and elongation = 14%). Ardakani et al [ 179 ] reported the effects of the addition of 0.1 wt% of Mn on the microstructure ( Fig. 4 c–d) and tensile properties of binary Zn-0.05 Mg alloys.…”
Section: Microstructure Textural Evolution and Mechanical Propertiementioning
confidence: 99%
“…1.1 9 10 À3 361 423 5.2 Liu et al [23] Cold Deformation Processes Hot Extrusion + Cold Drawing Zn-0.02Mg 1 9 10 À3 388 ± 2 455 ± 2 5.4 ± 0.3 Wang et al [24] Hot Extrusion + Cold Drawing Zn-0.08Mg after 0 days 3.3 9 10 À3 250 266 30 Jin et al [25] Zn-0.08Mg after 1 year 3. [26] Cold Rolling Zn-0.5Cu-0.05Mg 2 9 10 À3 241 ± 5 312 ± 2 44± 2 Ardakani et al [27] Hot Rolling + Cold Rolling Zn-4Cu 1 mm/min 327 393 39 Li et al [28] Hot-Warm (100°C ) Rolling…”
Section: Hot Extrusionmentioning
confidence: 99%
“…The addition of Mg to Zn matrices resulted in the formation of hypoeutectic microstructures. These microstructures are comprised of α-Zn dendrites and a eutectic mixture of α-Zn and Mg 2 Zn 11 phases [ 71 , 77 , 78 , 79 ]. The presence of intermetallic particles (Mg 2 Zn 11 ) due to the addition of Mg in Zn significantly enhanced the mechanical properties of Zn matrices.…”
Section: Zn-based Biomaterialsmentioning
confidence: 99%